2011
DOI: 10.1186/1471-2156-12-47
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of porcine IGF2 imprinting status to DNA methylation at the H19 DMD and the IGF2 DMRs 1 and 2

Abstract: BackgroundPorcine IGF2 and the H19 genes are imprinted. The IGF2 is paternally expressed, while the H19 gene is maternally expressed. Extensive studies in mice established a boundary model indicating that the H19 differentially methylated domain (DMD) controls, upon binding with the CTCF protein, reciprocal imprinting of the IGF2 and the H19 genes. IGF2 transcription is tissue and development specific involving the use of 4 promoters. In the liver of adult Large White boars IGF2 is expressed from both parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…This result is not related to poor identification and localization in swine of IGF2 and H19 DMRs, which are highly homologous to the corresponding human gene cluster and well described in the literature [50,51]. Moreover, our results are in accordance with a study on bovine sperm that did not find any significant difference in the methylation level of IGF2/H19 DMRs of high-or low-fertility bulls [52].…”
Section: Differences In Methylation Levels Between Normal and Low-semsupporting
confidence: 95%
“…This result is not related to poor identification and localization in swine of IGF2 and H19 DMRs, which are highly homologous to the corresponding human gene cluster and well described in the literature [50,51]. Moreover, our results are in accordance with a study on bovine sperm that did not find any significant difference in the methylation level of IGF2/H19 DMRs of high-or low-fertility bulls [52].…”
Section: Differences In Methylation Levels Between Normal and Low-semsupporting
confidence: 95%
“…In this study, we detected significant hypermethylation on DMR1 and DMR2 of the IGF2 locus in the hippocampus of prenatally betaine-supplemented piglets. It is well known that IGF2 gene is imprinted to express exclusively from the paternal allele in most fatal tissues in various mammalian species including pigs [48]. However, biallelic expression or relaxation of IGF2 imprinting appears to be a common feature in adult porcine tissues [49].…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid deficiency may prevent normal methylation of epigenetically regulated IGF-2 gene. Since its expression is regulated by DNA methylation, it may be vulnerable to abnormal methylation during development [19-20]. A number of studies have also demonstrated that maternal supplementation with folic acid increased the methylation of the IGF-2 gene in the rat liver [21] and human blood offspring [22].…”
Section: Introductionmentioning
confidence: 99%